Technical note and surgical outcomes of percutaneous cable fixation in subtrochanteric fracture: A review of 51 consecutive cases over 4 years in two institutions. Issue 2 (February 2019) - Shin, Won Chul; Moon, Nam Hoon; Jang, Jae Hoon; Jeong, Jae Yoon; Suh, Kuen Tak
Highlights: Cerclage wiring for treatment of subtrochanteric femoral fractures with long oblique or spiral fracture lines has been accepted as a good surgical technique to minimize fracture gap and improve fracture stability. However, cerclage wiring technique is at risk for wire breakage or difficulty achieving full compression of the fracture site in high-energy subtrochanteric femoral fractures because of the relatively lower biomechanical properties of wire. Percutaneous cerclage cable fixation can provide a greater likelihood of achieving anatomical reduction and increased stability of fracture, while preserving biology around the fracture site. We believe that percutaneous cerclage cable fixation can be an effective surgica l technique for the treatment of complex subtrochanteric fractures. Abstract: Background: The main purpose of this study is to introduce our surgical technique and report surgical outcomes for percutaneous cable fixation in the treatment of subtrochanteric femoral fractures. Methods: Between May 2013 and April 2017, 51 patients with subtrochanteric femoral fractures treated with closed intramedullary nailing and percutaneous cable fixation were enrolled in this study. Postoperative angulation, union rate, time from injury to union, and femoral shortening were also evaluated to assess radiologic outcomes. Clinical outcomes, including range of hip flexion, walking ability, and Harris hip score at the last follow-up were evaluated. Results: Average coronal and sagittal angulation after surgery were 0.9 (range 0–5) and 0.3 (range 0–5), respectively. There was no postoperative angulation of more than 5°. Average shortening of the femur at 1-year follow-up was 2.7 mm (range 0–15). Bone union was achieved in 50 patients (98.0%) and average time to union was 18.6 weeks (range 12–48). Hip flexion, walking ability and Harris hip score at the last follow up were 115.6° (90–120), 7.9 (5–9), and 88.3 (65–100), respectively. Conclusion: Percutaneous cerclage cable fixation can provide a greater likelihood of achieving anatomical reduction and increased stability of fracture, while preserving biology around the fracture site. Thus, percutaneous cerclage cable fixation can be an effective surgical technique for the treatment of complex subtrochanteric fractures.